Local and Systemic IL-7 Concentration in Gastrointestinal-Tract Cancers - Iwona Bednarz-Misa; Dorota Diakowska; Małgorzata Krzystek-Korpacka (Medicina, 2019)
Background and objectives: Interleukin-7 (IL-7) is exploited in cancer immunotherapies although its status in solid tumors is largely unknown. We aimed to determine its systemic and local concentrations in esophageal (EC), gastric (GC), and colorectal (CRC) cancers. Materials and Methods: IL-7 was immunoenzymatically measured in paired surgical specimens of tumors and tumor-adjacent tissue (n = 48), and in the sera of 170 individuals (54 controls and 116 cancer patients). Results: IL-7 was higher in tumors as compared to noncancerous tissue in all cancers (mean difference: 29.5 pg/g). The expression ratio (tumor to normal) was 4.4-fold in GC, 2.2-fold in EC, and 1.7-fold in CRC. However, when absolute concentrations were compared, the highest IL-7 concentrations were in CRC, both when tumor and noncancerous tissue were analyzed. In CRC tumors, IL-7 was 2 and 1.5 times higher than in EC and GC tumors. In noncancerous CRC tissue, IL-7 was 2.3- and 2.8-fold higher than in EC and GC. IL-7 overexpression was more pronounced in Stage 3/4 and N1 cancers as a result of decreased cytokine expression in noncancerous tissue. Tumor location was a key factor in determining both local and systemic IL-7 concentrations. Serum IL-7 in CRC and EC was higher than in controls, GC, and patients with adenocarcinoma of gastric cardia (CC), but no significant correlation with the disease advancement could be observed. Conclusions: IL-7 protein is overexpressed in EC, GC, and CRC, but concentrations differ both in tumor and tumor-adjacent tissue with respect to tumor location. More advanced cancers have lower IL-7 concentrations in the immediate environment of the tumor. At the systemic level, IL-7 is elevated in CRC and EC, but not CC or GC. IL-7 dependence on the location of the primary tumor should be taken into account in future IL-7-based immunotherapies. Functional studies explaining a role of IL-7 in gastrointestinal cancers are needed.